Risk-Neutral Models for Emission Allowance Prices and Option Valuation - Carmona, René; Hinz, Juri (Management Science, 2011)
The existence of mandatory emission trading schemes in Europe and the United States, and the increased liquidity of trading on futures contracts on CO 2 emissions allowances, led naturally to the next step in the development of these markets: These futures contracts are now used as underliers for a vibrant derivative market. In this paper, we give a rigorous analysis of a simple risk-neutral reduced-form model for allowance futures prices, demonstrate its calibration to historical data, and show how to price European call options written on these contracts. This paper was accepted by Haitao Li, guest editor, finance.